Electronic Structure Engineering of LiCoO2 toward Enhanced Oxygen Electrocatalysis. Issue 16 (5th March 2019) - Zheng, Xiaobo; Chen, Yaping; Zheng, Xusheng; Zhao, Guoqiang; Rui, Kun; Li, Peng; Xu, Xun; Cheng, Zhenxiang; Dou, Shi Xue; Sun, Wenping
Abstract: Developing low‐cost and efficient electrocatalysts for the oxygen evolution reaction and oxygen reduction reaction is of critical significance to the practical application of some emerging energy storage and conversion devices (e.g., metal–air batteries, water electrolyzers, and fuel cells). Lithium cobalt oxide is a promising nonprecious metal‐based electrocatalyst for oxygen electrocatalysis; its activity, however, is still far from the requirements of practical applications. Here, a new LiCoO2 ‐based electrocatalyst with nanosheet morphology is developed by a combination of Mg doping and shear force‐assisted exfoliation strategies toward enhanced oxygen reduction and evolution reaction kinetics. It is demonstrated that the coupling effect of Mg doping and the exfoliation can effectively modulate the electronic structure of LiCoO2, in which Co 3+ can be partially oxidized to Co 4+ and the Co–O covalency can be enhanced, which is closely associated with the improvement of intrinsic activity. Meanwhile, the unique nanosheet morphology also helps to expose more active Co species. This work offers new insights into deploying the electronic structure engineering strategy for the development of efficient and durable catalysts for energy applications. Abstract : A new LiCoO2 ‐based electrocatalyst with nanosheet morphology is designed by the coupling of Mg doping and shear‐assisted exfoliation strategies toward enhanced oxygen electrocatalysis kinetics. The improved catalytic activity can be attributed to the optimized electronic structure of Co and Co–O covalency, enhanced charge transfer ability, and abundant exposure of active sites.